(untitled) - Weston, Jack; 1924-1996.; Brucker, Jane.; Price, Lonny; Cantor, Max.; Bishop, Kelly; Rhodes, Cynthia; Swayze, Patrick; Orbach, Jerry; Gottlieb, Linda; (Producer); Bergstein, Eleanor; et al. (Santa Monica, Calif., 2007)
The summer of 1963 innocent 17-year-old Baby vacations with her parents at a Catskills resort. One evening she is drawn to the staff quarters by stirring music. There she meets Johnny, the hotel dance instructor, who is as experienced as Baby is naive. Baby soon becomes Johnnys pupil in dance and love.
Keywords: Catskill Mountains; Drama; Resorts; Catskill Mountains; New York (State); Drama; New York (State); New York (State); Drama; New York (State); Resorts; Drama; Catskill Mountains; Man-woman relationships; Dance teachers; Drama; Catskill Mountains (N.Y.); Musical; Feature; Romance; Feature; Drama; Musical films; Feature films; Video recordings for the hearing impaired; Dance drama